Diabetes risk factor screening in adults using perkeni questionnaire and oral glucose tolerance test in socah county, bangkalan - Kamal, Radin H; Novendrianto, Dwiki; Chadijah, Faizah; Prasetya, Galan Budi; Pratama, Gilang Satria; Ariadnya, Mentari Octarina; Larasati, Nikita Gladys; Darain, Nur Lia F; Nanda, Ovitrani; Mavita, Silvi; Usamah, Usamah; Prajitno, Jongky Hendro (Folia Medica Indonesiana, 2017)
There are 8.4 million diabetes adult patients in Indonesia and most remained undiagnosed. Screening process for diabetes is very important. PERKENI has recommended the use of questionnaire and Oral Glucose Tolerance Test (OGTT) as risk factor screening tools. This study aimed to find out the use of PERKENI questionnaire and OGTT in adults as diabetes risk factor screening tools. This was a descriptive cross sectional study conducted in 2015 in Socah County Bangkalan. Participants (n=91) were interviewed regarding diabetes risk factor using PERKENI questionnaire. Anthropometric (height, weight, and abdominal circumference) measurements were also taken. The results were categorized into: very low risk, increased risk, moderate risk and high risk. Only those categorized as high risk were asked to take OGTT. Exclusion criteria were participants who had been diagnosed with diabetes by a physician and/or routinely taking anti diabetic medication, consumed drugs during the previous two weeks and does not finish the required procedures. From 91 eligible participants, only 9 (9.89%) were categorized as high risk. The result of OGTT were: 4 were within normal limit, 1 had impaired glucose tolerance (IGT) and 4 were newly diagnosed with diabetes. The use of PERKENI questionnaire and OGTT in high risk adult population as a diabetes risk factor screening tool increased new findings of diabetes cases. Our analysis may support the adoption of diabetes risk factor screening methods through questionnaires and OGTT in high risk adult population, especially in low resource setting.